2014
DOI: 10.1007/s12663-014-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Incision Biopsy for Diagnosis of Oral Verrucous Carcinoma: A Multivariate Clinicopathological Study

Abstract: Introduction Studies have reported 20 % of conventional squamous cell carcinoma in patients with verrucous carcinoma (VC), later these cancers were termed as hybrid VC. It is important to distinguish both while planning treatment since hybrid VC requires addressing regional lymphatics in addition to respective surgery. Information on odds of missing the foci of invasion on routine incision biopsy might be useful in this regard. Patients and MethodsRecords of all the patients surgically treated for oral cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Shear and Pindborg similarly described deep epithelial projections into subcutaneous tissue without invasion in VC as compared with superficial projections in VH . To complicate the diagnostic pursuit, recent studies have demonstrated the poor reliability of incisional biopsy to reach a diagnosis of VC and the notable possibility of hybrid neoplasms within lesions . Nevertheless, our analysis of this cohort adds an important contribution to the understanding of prognostic factors in oral cavity VC.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Shear and Pindborg similarly described deep epithelial projections into subcutaneous tissue without invasion in VC as compared with superficial projections in VH . To complicate the diagnostic pursuit, recent studies have demonstrated the poor reliability of incisional biopsy to reach a diagnosis of VC and the notable possibility of hybrid neoplasms within lesions . Nevertheless, our analysis of this cohort adds an important contribution to the understanding of prognostic factors in oral cavity VC.…”
Section: Discussionmentioning
confidence: 70%
“…28 To complicate the diagnostic pursuit, recent studies have demonstrated the poor reliability of incisional biopsy to reach a diagnosis of VC and the notable possibility of hybrid neoplasms within lesions. 29 Nevertheless, our analysis of this cohort adds an important contribution to the understanding of prognostic factors in oral cavity VC. To our knowledge, this report is the first population-based analysis of prognostic factors affecting survival outcomes in patients with oral cavity VC.…”
Section: Discussionmentioning
confidence: 96%
“…[ 6 7 ] They are slow growing tumors known to have low metastatic potential with good prognosis. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…however, the proportion of conventional OVC component may vary and the prognosis of hybrid VC with high proportion of OVC may have better prognosis than OSCC. Due to high similarity in staging and grading, incision biopsy is extremely unreliable to diagnose and differentiate oral hybrid VC from OVC (86). For diagnosis of this hybrid tumor, it is necessary to examine an adequate biopsy sample extending to the underlying bone for examination of the periosteum and the mucosa-connective tissue interface.…”
Section: Ovc and Oral Squamous Papilloma (Osp)mentioning
confidence: 99%